Three new species of the Simulium (Simulium) striatum species-group (Diptera: Simuliidae) from Thailand, with their phylogenetic relationships - Kittipat Aupalee (2020)
© 2020 Elsevier B.V. Three new species of black flies from Thailand, Simulium wangkwaiense, S. tadtonense and S. maeklongkeense, are described based on their adults, pupal exuviae and cocoons. All three new species are assigned to the Simulium (Simulium) striatum species-group, bringing its total number in Thailand to seven. Simulium wangkwaiense sp. nov. is the species formerly called S. quinquestriatum in Thailand. Certain male and pupal morphological characteristics are shown to separate all seven Thai species of this species-group. All of the three new species have been analyzed genetically for their phylogenetic relationships, with three known related species (except for S. thailandicum), by using the fast-evolving nuclear big zinc finger (BZF) gene.